PENGARUH PENDEKATAN PEMBELAJARAN VISUAL THINKING DALAM MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIKA SISWA SD - Muhammad Fendrik; Roby Maiva Putra (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2018)
The purpose of this study is to examine the influence of visual thinking approach to the mathematical connections ability. The method is quasi experiments with the design of this non-equivalent control group involved 66 students of fifth grade in one of the Elementary Schools in Pekanbaru. The instrument used is a matter of pretest and post test. The statistical analysis was a two-track ANOVA test and non-parametric Kruskal-Wallis test. The result of the research are: 1) improving students’ mathematical connection ability who get learning with visual thinking approach was not significantly different than students who get conventional learning; 2) there is no interaction between learning (visual thinking and conventional) with students' mathematical abilities (upper, middle and lower) on the improving students’ mathematical connection ability; and 3) there are differences in students’ mathematical connection ability who gain learning with visual thinking approach in terms of mathematical ability of students (top, middle and bottom).